Hubungan Penerimaan Diri Dengan Harga Diri Pada Remaja Pasca Perceraian Orang Tua Pada Siswa SMP Negeri 1 Kabila Kabila Kabupaten Bone Bolango - Hafni Van Gobel; Gusti Agung Ayu Putri Ariani; Muhammad Fadlun Utiarahman (Poltekkes Kemenkes Gorontalo, 2021)
Background:Parents separation can deteriorate children’s achievement at school, they also tend to be naughty or have low self-esteem. Low self-esteem is a negative feeling toward oneself including losing self-confidence, worthless, useless, helpless, pessimistic, no hope, and desperate. Other than self-esteem, teenagers’ self-acceptance toward parents’ divorce. Self-acceptance is one of the happiness cores, either self-acceptance or environmental acceptance. Objective:This research aims to find out the relationship between self-acceptance and self-esteem on teenagers after parents’ divorce on students of SMP Negeri 1 Kabila, Bone Bolango District. Method:This research applies a survey research method using a chi-square statistical test. The independent variable is self-acceptance, while the dependent variable is self-esteem. The sample is the total of the entire population, which is 64 students. The sampling technique applies a total sampling technique. Results:The data analysis using chi-square statistical test obtains X2 count is 64,000 higher than X2 table with p-value = 0,000 (<0,05) using df 1, which means H0 is rejected, and Ha is accepted. Conclusion: From the result, it can be seen that there is a significant relationship between self-acceptance and self-esteem on teenagers after parents’ divorce on students of SMP Negeri 1 Kabila, Bone Bolango District.